Antioxidant Properties of Berberis aetnensis C. Presl (Berberidaceae) Roots Extract and Protective Effects on Astroglial Cell Cultures - Agata Campisi; Rosaria Acquaviva; Roberta Bonfanti; Giuseppina Raciti; Andrea Amodeo; Silvana Mastrojeni; Salvatore Ragusa; Liliana Iauk (The Scientific World Journal)
Berberis aetnensis C. Presl (Berberidaceae) is a bushy-spiny shrub common on Mount Etna (Sicily). We demonstrated that the alkaloid extract of roots of B. aetnensis C. Presl contains prevalently berberine and berbamine, possesses antimicrobial properties, and was able to counteract the upregulation evoked by glutamate of tissue transglutaminase in primary rat astroglial cell cultures. Until now, there are no reports regarding antioxidant properties of B. aetnensis C. Presl collected in Sicily. Air-dried, powdered roots of B. aetnensis C. Presl were extracted, identified, and quantified by HPLC. We assessed in cellular free system its effect on superoxide anion, radicals scavenging activity of antioxidants against free radicals like the 1,1-diphenyl-2-picrylhydrazyl radical, and the inhibition of xanthine oxidase activity. In primary rat astroglial cell cultures, exposed to glutamate, we evaluated the effect of the extract on glutathione levels and on intracellular production of reactive oxygen species generated by glutamate. The alkaloid extract of B. aetnensis C. Presl inhibited superoxide anion, restored to control values, the decrease of GSH levels, and the production of reactive oxygen species. Potent antioxidant activities of the alkaloid extract of roots of B. aetnensis C. Presl may be one of the mechanisms by which the extract is effective against health disorders associated to oxidative stress.